The clinical features of anti-CNTN1 antibodies associated autoimmune nodopathies with nephropathy: a case series - Jinping Wan; Tiegen Xiong; Jianian Hu; Shaojun Liu; Jie Lin; Chongbo Zhao; Chong Sun; Hai Xiao (Frontiers in Neurology, 2026)
Objective The concurrence of anti-contactin-1 (CNTN1) antibody-associated autoimmune nodopathies (AN) and nephropathy has been sporadically reported, though the underlying relationship remains unclear. This case series study aimed to investigate the clinical characteristics and renal pathology of anti-CNTN1 antibody-associated AN with nephropathy. Methods A retrospective case series was conducted including 69 patients diagnosed with AN, among whom 11 patients tested positive for anti-CNTN1 antibodies. Clinical manifestations, electrophysiological data, laboratory results, and renal biopsy findings were collected and analyzed. The presence of nodal/paranodal antibodies was confirmed using serum cell-based assays. Renal biopsies were performed in four patients, with immunohistochemical and immunofluorescence staining, including CNTN1 staining, to characterize renal pathology. Results Compared to patients with non-anti-CNTN1 antibody-associated AN, the anti-CNTN1 antibody group had a significantly lower proportion of males (54.5% vs. 84.5%, p = 0.024) but showed higher rates of hypertension (36.4% vs. 8.6%, p = 0.021) and positive autoimmune antibodies (50% vs. 5%, p < 0.001). This group also exhibited a markedly higher prevalence of proteinuria (63.6% vs. 10.3%, p < 0.001) and nephropathy (63.6% vs. 3.4%, p < 0.001). Among anti-CNTN1 antibody-positive patients, females were more prone to concomitant nephropathy. Patients with both conditions exhibited onset ages ranging from 17 to 67 years, with a chronic course, frequent positive Romberg’s sign, and prolonged distal motor and F-wave latencies. Renal biopsy in four patients revealed membranous nephropathy (MN) in three cases and lupus nephritis (LN) in one case. Notably, CNTN1 staining of kidney tissue was positive only in patients with anti-CNTN1 antibody-associated AN with MN. Conclusion Anti-CNTN1 antibody-associated AN patients have a higher prevalence of nephropathy compared to those AN without anti-CNTN1 antibodies. Females demonstrate a particularly higher risk of comorbid AN and nephropathy. Renal pathology in these patients is not limited to MN but can also include LN. These findings highlight a complex immunopathological relationship between anti-CNTN1 antibody-associated AN and nephropathy, warranting further studies to understand the underlying mechanisms.